Emerging and Traditional Technologies for Safe, Healthy and Quality Food - Nedović, Viktor; Raspor, Peter; Lević, Jovanka; Tumbas Šaponjac, Vesna; Barbosa-Cánovas, Gustavo V. (Food Engineering Series,, 2016)
Since its inception in 2002, the Central European Food Congress (CEFood) has been a biannual meeting intended for food producers and distributors as well as researchers and educators to promote research, development, innovation and education within food science and technology in the Middle European region with a tight connection to global trends. The 6th CEFood, held in Novi Sad, Serbia, May 23-26, 2012, highlighted the novel technologies and traditional foods aimed at both the European and global markets. Specifically, CEFood 2012 focused on the latest progress in fundamental and applied food science, research and development, innovative technology, food ingredients, novel trends in nutrition and health, functional and bioactive food, food engineering, food safety and quality and the food and feed market. This book will consist of contributions from various presenters at CEFood 2012, covering the major themes of this Congress. Chapters contributed by expert presenters fromthe 6th CEFood Congress of 2012 Highlights the novel technologies of food science Discusses the future of the food industry and food research.